2022
DOI: 10.1177/11795735221092516
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to healthy dietary pattern is associated with lower risk of multiple sclerosis

Abstract: Background Different studies have confirmed the role of nutritional factors in the etiology of Multiple sclerosis (MS). However, dietary patterns associated with the risk of MS remain unknown. Objectives This study aimed to investigate the possible relationship between the existing dietary patterns and the risk of MS. Methods This case-control study was conducted in Mashhad city, Iran in 2015. In total, 197 MS patients and 200 control subjects (matched in terms of age, gender, education level, and body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Several observational studies regarding the influence of diet on MS risk have considered diet at the time of MS onset or thereafter. [5][6][7][8][9] Some studies found that patients with MS tend to have a less healthy diet compared with controls. 4,5 An Australian study found that patients with a diagnosis of central nervous system demyelination consumed a diet with higher inflammatory index, based on the overall inflammatory effect of the diet, compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several observational studies regarding the influence of diet on MS risk have considered diet at the time of MS onset or thereafter. [5][6][7][8][9] Some studies found that patients with MS tend to have a less healthy diet compared with controls. 4,5 An Australian study found that patients with a diagnosis of central nervous system demyelination consumed a diet with higher inflammatory index, based on the overall inflammatory effect of the diet, compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Some studies found that patients with MS tend to have a less healthy diet compared with controls. 4,5 An Australian study found that patients with a diagnosis of central nervous system demyelination consumed a diet with higher inflammatory index, based on the overall inflammatory effect of the diet, compared with controls. 8 MD is based on consumption of high amounts of vegetables, fruits, nuts, fish and other sea food, and the use of olive oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets enriched in added sugars and processed foods corresponded with higher burden of metabolic risk factors including abdominal obesity and reduced circulating high-density lipoprotein concentrations among pwMS [140] . Case-control studies corroborated that pro-inflammatory and low antioxidant-containing diets increased MS risk [129,141–144] .…”
Section: Human Ms Dietary Studiesmentioning
confidence: 99%
“…Numerous MS studies have reported positive impacts of the Mediterranean diet and the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND). These dietary patterns and other diets with high intake of fruits and vegetables associated with reduced risk of MS [130,132,142] .The Mediterranean diet reduced fatigue and improved QoL in several trials [154][155][156][157][158][159] , and in a 6-month randomized controlled trial, reduced EDSS progression compared with controls among women with MS [155] . Adherence to the MIND diet associated with thalamic volume in a cross-sectional study among 180 individuals with early MS [133] .…”
Section: Dietary Patterns That Improve Msmentioning
confidence: 99%